2018
DOI: 10.1097/md.0000000000012645
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diet restriction on bowel preparation for colonoscopy

Abstract: Diet restriction is one of the difficult parts of bowel preparation for colonoscopy, and many patients do not follow instructions properly. Few studies have evaluated the impact of dietary restriction in real clinical setting. The aim of this study was to study the effect of diet control on bowel preparation with detailed investigation of unacceptable food list in order to reveal what kind of foods are most problematic in clinical practice.Prospective observational study was carried out at a university-affilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Diet restriction is also known to be a risk factor for bowel preparation [22]. Many studies had shown that clear liquid diet (fruit juices, sports drinks, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Diet restriction is also known to be a risk factor for bowel preparation [22]. Many studies had shown that clear liquid diet (fruit juices, sports drinks, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Las restricciones de la dieta hacen parte de la preparación del colon; y es frecuente que muchos pacientes no sigan estas recomendaciones adecuadamente (35) . En contraste, los pacientes del estudio aceptaron seguir la dieta recomendada baja en residuos (36) , en el 99 % de los casos.…”
Section: Discussionunclassified
“…Failure to complete a bowel preparation regimen is an important factor that affects the adequacy of bowel preparation. [1][2][3][4] Owing to the large volume and unpleasant taste of the conventional 4 L of polyethylene glycol electrolyte (PEG) lavage solution, low-volume purgatives with improved flavor and comparable efficacy and safety have been developed. [5][6][7][8][9][10] However, participants in clinical trials using low-volume agents were mainly healthy, young, or middle-aged.…”
Section: Introductionmentioning
confidence: 99%